2019
DOI: 10.1007/s41130-019-00090-y
|View full text |Cite
|
Sign up to set email alerts
|

Is there any gender gap in the production of legumes in Malawi? Evidence from the Oaxaca–Blinder decomposition model

Abstract: Understanding the gender differences in agricultural productivity is crucial for formulating informed and effective policies to sustainably improve low productivity which characterises agriculture in Sub-Sahara Africa. Using a panel dataset from the ICRISAT led Tropical Legumes project III (2008-2013), we analyse the gender gap in the production of legumes in Malawi. Employing the Oaxaca-Blinder decomposition method allows decomposition of gender gap into the following: (i) the portion caused by observable dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 22 publications
0
15
1
Order By: Relevance
“…The positive influence on the decision to grow legumes is supported by the long‐standing view that legumes, including groundnuts, are ‘women crops’ (Nakazi et al., 2017; Orr, Kambombo, Roth, Harris, & Doyle, 2015). Although our results support this, other findings in the region show that for the main legume grown in the area, groundnuts, households headed by women tend to allocate less land to it (Waldman, Ortega, Richardson, Clay, & Snapp, 2016) and are 20% less productive (Joe‐Nkamuke et al., 2019) than their male‐headed counterparts. The latter study, despite establishing a convincing empirical evidence, did not account for the influence of women in male‐headed households and used data from regions where legumes are grown as cash crops such as the Mchinji District of Malawi (Joe‐Nkamuke et al., 2019).…”
Section: Discussioncontrasting
confidence: 58%
See 2 more Smart Citations
“…The positive influence on the decision to grow legumes is supported by the long‐standing view that legumes, including groundnuts, are ‘women crops’ (Nakazi et al., 2017; Orr, Kambombo, Roth, Harris, & Doyle, 2015). Although our results support this, other findings in the region show that for the main legume grown in the area, groundnuts, households headed by women tend to allocate less land to it (Waldman, Ortega, Richardson, Clay, & Snapp, 2016) and are 20% less productive (Joe‐Nkamuke et al., 2019) than their male‐headed counterparts. The latter study, despite establishing a convincing empirical evidence, did not account for the influence of women in male‐headed households and used data from regions where legumes are grown as cash crops such as the Mchinji District of Malawi (Joe‐Nkamuke et al., 2019).…”
Section: Discussioncontrasting
confidence: 58%
“…However, in rural areas with unskilled labour, poor soils and variable production, the elasticity of substitution among production assets is high (Mburu, Ackello-Ogutu, & Mulwa, 2014). For instance, the role of women in legume cropping was deemed to be significant (Snapp, Rohrbach, Simtowe, & Freeman, 2002), but as the crops enter the market, men are more likely to take control (Joe-Nkamuke, Olagunju, Njuguna- Mungai, & Mausch, 2019).…”
Section: Concepts and Analytical Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are additional strands of literature that established that agricultural cooperatives influence market bargaining power and output prices which is a key motivation for farmers to increase output, productivity levels, and economic welfare. Rural farmers obtain relevant information on market prices and marketing channels through various associations to which they belong, thereby helping them with the sales of their produce and to realise higher price margin [ 10 , 21 , 34 , 38 , 39 ]. In summary, agricultural cooperatives through the provision of access to improved technologies and inputs facilitate optimal use of inputs which leads to increase in TE of farmers and consequently improved farm yield, while also through the provision of marketing information agricultural cooperatives ensures yield is better marketed thereby resulting to increased farm income and consequently overall welfare of agricultural households.…”
Section: Context and Related Literaturementioning
confidence: 99%
“…Decomposing wage and income dissimilarity among men and women is a phenomenon more nuanced in labour economics [1][2][3][4][5], cumulatively pointing towards women's plots but pointed that these differences were crop-dependent as most men preferred cash lucrative crops compared to women who seemed to prefer crops consumed within households. Again, a paper from Malawi on legumes by Joe-Nkamuke et al [20] revealed that groundnut cultivated on women-owned plots saw 28 percent less productivity compared to men's.…”
Section: Introductionmentioning
confidence: 99%